1998
DOI: 10.1098/rspb.1998.0546
|View full text |Cite
|
Sign up to set email alerts
|

A massively connected subthalamic nucleus leads to the generation of widespread pulses

Abstract: A composite model of the subthalamic nucleus is developed from physiological and anatomical considerations. First, study of a geometric model of the anatomical arrangements of projection neurons within the nucleus indicates that they form a massively connected network. Second, given the excitatory nature of these neurons, their threshold and peak firing rates, a simple model of neuron responses reveals that large regions of this highly interconnected nucleus can respond to excitatory input in the form of a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…11). The parafascicular thalamic nucleus probably plays a critical role in this function, because it receives input from the SC and projects to the subthalamic nucleus, a site that provides widespread excitatory input to the inhibitory basal ganglia output channels represented in the substantia nigra and the internal globus pallidus/entopeduncular nucleus (Mouroux and Feger, 1993;Gillies and Willshaw, 1998;Redgrave et al, 1999). A short latency, excitatory input relayed from the SC to the parafascicular nucleus and on to the subthalamus would have the effect of closing currently disinhibited channels in the basal ganglia output nuclei (Chevalier and Deniau, 1990).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…11). The parafascicular thalamic nucleus probably plays a critical role in this function, because it receives input from the SC and projects to the subthalamic nucleus, a site that provides widespread excitatory input to the inhibitory basal ganglia output channels represented in the substantia nigra and the internal globus pallidus/entopeduncular nucleus (Mouroux and Feger, 1993;Gillies and Willshaw, 1998;Redgrave et al, 1999). A short latency, excitatory input relayed from the SC to the parafascicular nucleus and on to the subthalamus would have the effect of closing currently disinhibited channels in the basal ganglia output nuclei (Chevalier and Deniau, 1990).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…If so, this would provide a mechanistic basis for why unexpected events lead to disruptions of ongoing cognitive processing (Escera et al, 1998; Schröger and de Fockert et al, 2004). While such effects are often explained by attentional reorienting, as indexed by an enlarged P3a-ERP (Courchesne et al, 1975;Ranganath and Rainer, 2003;Polich, 2007), our study provides an elaboration; this attentional reorienting could be underpinned by a global inhibitory signal induced by the unexpected event, which then affects ongoing cognitive processing.…”
Section: Why Unexpected Events Produce Distractibilitymentioning
confidence: 99%
“…In the laboratory, motor slowing following unexpected events is a ubiquitous finding. It occurs after unexpected perceptual events (hereafter referred to as "novels"; Barcelo et al, 2006;Parmentier et al, 2008;Vachon et al, 2012), action errors (Rabbitt, 1966;Laming, 1979;Debener et al, 2005;Jentzsch and Dudschig, 2009;Eichele et al, 2010;King et al, 2010;Logan and Crump, 2010), unexpected action effects (Gentsch et al, 2009;Wessel et al, 2012), and reward prediction errors (Cavanagh et al, 2010). Given the pervasiveness of such motor slowing, there is considerable interest in the underlying mechanism(s) (Marco-Pallarés et al, 2008;Notebaert et al, 2009;Danielmeier and Ullsperger, 2011;Parmentier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, only the models of Wickens et al 33 capture detailed anatomy within a single nuclei. Recent models of the STN and GPe 16,43 have demonstrated that the anatomic arrangements within a nucleus can be crucial to how the nucleus operates within the basal ganglia as a whole. Models of lateral connectivity within the STN demonstrate that this can functionally lead to widespread switch-like behavior across the nucleus.…”
Section: Discussionmentioning
confidence: 99%